Analysis of the Decline in Indonesian Coal Exports to China during the Covid-19 Pandemic between 2019 and 2020 - Danial Darwis; Samuel Sigit Irwanto (Papua Journal of Diplomacy and International Relations, 2023)
This study analyses the decline in Indonesian coal exports to China during the Covid-19 pandemic from 2019 to 2020. The timeframe was selected due to a decline in Indonesian coal exports to China during that period. Although literature reviews indicate that several previous articles have discussed Indonesia’s coal exports to China, they do not cover the timeframe during the Covid-19 pandemic, as is the case in this study. Consequently, this article is novel and contributes to the discussion in that area. This study was conducted qualitatively, as well as using the library research method to collect information from a variety of secondary sources. The findings of this study indicate that the decline in Indonesian coal exports to China during the Covid-19 pandemic from 2019 to 2020 occurred as the result of China’s domestic problems. These domestic problems include the decline in production in China’s industry because of the lockdown policy carried out during the pandemic. The pandemic significantly limited import activities and slowed down domestic production, in addition to the overall slowdown of the world economy which led to a decrease in demand for coal. All these factors affected supply from Indonesia.KEYWORDSCoal Export; China; Covid-19; Indonesia